Lower lung cancer rates in Jewish smokers in Israel and the USA. Issue 9 (18th May 2015) - Rennert, Gad; Kremer, Ran; Rennert, Hedy S.; Wollner, Mira; Agbarya, Abed; Pinchev, Mila; Lejbkowicz, Flavio; Spitz, Margaret R.; Muscat, Joshua E.
<x xml:space="preserve">Abstract</x> Lung cancer rates in Israeli Jews have remained stable over the last five decades and are much lower than in most developed countries despite high historical smoking rates. We compared lung cancer risk in Jews and non‐Jews in Israel and in the United States. Data were derived from a population‐based, case–control study in Israel (638 cases, 496 controls) to estimate lung cancer risk associated with smoking. Data were also acquired from a case–control study in the United States with information on religious affiliation (5, 093 cases, 4, 735 controls). Smoking was associated with lung cancer risk in all religion/gender groups in both studies. However, major differences in risk magnitude were noted between Jews and non‐Jews; ever smoking was associated with a moderately elevated risk of lung cancer in Jewish men and women in Israel (OR = 4.61, 2.90–7.31 and OR = 2.10, 1.36–3.24, respectively), and in Jewish men and women in the United States (OR = 7.63, 5.34–10.90 and OR = 8.50, 5.94–12.17) but were significantly higher in Israeli non‐Jewish men (OR = 12.96, 4.83–34.76) and US non‐Jewish men and women (OR = 11.33, 9.09–14.12 and OR = 12.78, 10.45–15.63). A significant interaction between smoking and religion was evident in light, moderate and heavy male and female smokers. The differences in risk level between Israeli Jews and non‐Jews could not be explained by lung cancer genetic risk variants which were identified in GWAS (genes in the CHRNA5, TERT and CLPTM1L regions). Data from the two studies support the notion of a reduced risk of lung cancer in Jewish compared to non‐Jewish smokers in different areas of the world.